The measurement of group differences in social concepts - Morsbach, Gisela W L (Rhodes University, Faculty of Humanities, Department of Psychology, 1968)
The present study attempted a cross-cultural investigation of ethnic and national stereotypes in South Africa, a land inhabited by a heterogeneous population. In this country, real or imagined differences due to racial characteristics profoundly influence social interaction. Moreover, such differences are entrenched and underscored by the prevailing legal system while supplying the rationale for many actions of the goverru:tent in power. On the basis of relevant literature it was assumed that differentiation between stereotypes would be based mainly on colour, but that further distinctive differentiations would be present inside the ensuing major groupings ("White and "Non-White"). It was furthermore attempted to show that various groups differed significantly in their judgment of an ethnic stereotype only if they had a dissimilar relationship with the group to be judged. Altogether 760 subjects were tested. These belonged to the six major ethnic and cultural groups in South Africa (Africans, Afrikaners, Coloureds, English-speaking White Gentiles, Indians, and Jews). They were all asked to judge each one of ten concepts by means of the semantic differential technique, which consisted of twenty adjective pairs. Six of these concepts were the names of the South African groups mentioned above, while another three concepts represented the names of groups outside South Africa ("the Americans", "the Germans", and "the Russians") which play an important role in the thinking of South Africans. Finally, the subjects were asked to rate themselves ("Me"- concept). For the sake of better comparison, only first-year students were tested at various universities. The results were analyzed with the aid of a computer (the ICT computers at the University of Cape Town and at Rhodes University). Since a cross-cultural study rests on the theoretical assumption that any tests used for the purpose of comparison are reliable and valid in all cultures to be investigated, a few additional questions had to be asked. The checks undertaken confirmed that in the present study:- 1) The motivation of the subjects as well as their comprehension of the test's basic aims did not differ to any great extent. 2) The six groups did not differ appreciably as regards the social desirability of adjectives used, the semantic structure of the adjective pairs, and the range of scores on the adjective pairs. Furthermore, it was established that male-female differences in attitudes in each of the six groups tested were negligible. The stereotypes were compared with each other inside every one of the groups tested, as well as being compared between all the groups. These comparisons were carried out on the single adjective pairs separately (by means of the Sign Test and the Median Test), and then undertaken in the context of the factorial structure of the concepts. The major results showed that:- 1. The 'colour line' is an important criterion of evaluation in all groups but the Coloureds and the Jews. a) Apart from a 'Black Factor', on which the concepts "the Africans" and "the Coloureds" obtained high loadings, there appeared to be two factors dealing with the evaluation of the White groups. b) The evaluation of the 'Black Factor' by the African subjects was much more positive than the 'Black Factor' found in other groups. c) The Indian subjects did not regard themselves as belonging to the ' Non-Whites' ; neither were they regarded as such by the other subjects tested. 2. The criterion of colour was of less importance in the Coloured and Jewish groups tested. 3. The Jewish subjects appeared to possess the most differentiated stereotype structure, since, in their case, there were four, instead of the usual three factors to be extracted. Moreover, they tended to regard the Non-'White groups more positively than did the other two White groups. 4. The Afrikaans subjects held the most negative opinion of "the Africans"; conversely, "the Afrikaners" were also rejected more strongly than the English-speaking Whites by the Non-Whites tested. 5. Of all groups rated, "the Americans" were the most liked. 6. The stereotypes of "the Russians" and "the Germans" were fairly similar, except in the case of the Afrikaans subjects, who had an exceptionally positive regard for "the Germans". 1. Ratings of the subjects' own group were generally very much more positive than the ratings of the same group by members of other groups, except in the case of the English-speaking White Gentiles. 8. When any two groups rated a concept differently, this could generally be traced back to, on the one hand, differences in the relationships between each one of the judging groups, and, on the other, the group being judged. In conclusion it can be stated that differences between the groups as regards any one stereotype were generally smaller than the differences between the stereotypes of different concepts as held by any one group tested. Where no special relationships existed between a judging group and one being judged, ethnic and national stereotypes tended to be relatively similar in the various cultures and sub-cultures investigated.
Keywords: Ethnic groups -- Psychology -- South Africa; Racism -- South Africa; Stereotypes (Social psychology); Cross-cultural studies